From Labelling to Radio Broadcasting: Display during the “Socialist Reconstruction of the Hermitage” - Efits, Andrey A. (Actual Problems of Theory and History of Art, 2022)
The article focuses on display techniques introduced in the Hermitage during the so-called “Socialist Reconstruction” of the first half of the 1930s, under the directorship of Boris Legran. Rearrangement of the museum, based on Marxist “socio-economical formations” aimed at a mass audience, is usually considered to have been the product of propaganda, and the result of repressive state measures imposed upon the Hermitage in the years of the Cultural Revolution. Explanatory labelling, “composite” displays of different arts, plans for radio broadcasting in exhibition spaces and musical concerts at the Hermitage Theatre are here studied within the wider, transnational context to show that the transformations at the Hermitage were largely modelled on socially-oriented museological reforms in the US and Europe. It is also demonstrated that educational displays in the Hermitage and other Soviet art museums attracted many curators and art practitioners abroad, most notably in France, and may have influenced the introduction of similar practices in the West.